Pengembangan Multimedia Pembelajaran Interaktif Berbasis Scientific Approach Menggunakan Macromedia Flash untuk Meningkatkan Kemampuan Pemecahan Masalah Matematika - Indri EkaYulia Sari; Irwan Irwan; Edwin Musdi; Yerizon Yerizon (PendIPA Journal of Science Education, 2022)
This research was a development research using the Plomp model with 3 phases, namely preliminary research consisting of: needs analysis, curriculum analysis, concept analysis and analysis of student characteristics. The development or prototyping phase consists of: self evaluation and expert review, one-to-one evaluation and small group evaluation. And the assessment phase consists of testing the effectiveness by testing the results of learning mathematics. The results of this study indicate that the average score of the material aspect by mathematicians is 85.84%; educational technology expert 81.82%; and linguists 93.75%. Therefore, multimedia obtained a total average score of 89.10% or very valid criteria. Based on the multimedia practicality test conducted by an educator and 6 students, it shows that multimedia gets an average score of 86.15% or very practical criteria with an average of 81.67% by the teacher's response and 90.63% by the student's response. Based on the multimedia effectiveness test by giving math problem solving test questions obtained 78.26% of students who meet completeness, this shows that multimedia mathematics meets the criteria of being very valid, very practical and very effective for improving mathematical problem solving for students of MTs Muhammadiyah Class VIII.